La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.